ANALISIS PENGARUH PROFITABILITY, NET WORKING CAPITAL, LIQUIDITY, FIRM SIZE, LEVERAGE, DAN GROWTH OPPORTUNITY TERHADAP CASH HOLDING - Andra Syahrul Ramadhan; Fatchan Achyani (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to analyze the effect of profitability, net working capital, liquidity, firm size, leverage, growth opportunity on cash holding. The population in this study are energy companies listed on the IDX in 2021-2023. The research sample was determined using purposive sampling method and obtained a sample of 38 companies. The data used is data from the official IDX website and the website of each company. The analysis method used is multiple linear regression analysis models. The results of this study indicate that profitability, net working capital, and liquidity have a positive and significant effect on cash holding. Growth opportunity has a negative and significant effect. Meanwhile, firm size and leverage have no effect on cash holding.